Association of environmental water iodine concentration with abnormal circulating liver function indicators in a cross-sectional chinese population study - Yun Chen; Xinyi Bai; Yanhong He; Wenjing Che; Zheng Zhou; Haiyan Gao; Yan Zhang; Yao Chen; Qingzhen Jia; Lixiang Liu; Hongmei Shen (Ecotoxicology and Environmental Safety, 2025)
Previous studies have established a correlation between thyroid dysfunction and liver diseases. Environmental Water Iodine, a crucial source of iodine intake, has shown a U-shaped relationship with the occurrence of thyroid diseases. Nevertheless, the precise connection between different environmental water iodine concentrations (WIC) and liver function remains unclear.Thus, a cross-sectional study was conducted in regions with varying levels of unimproved water supplies, categorized by WIC: < 10 µg/L, 40–100 µg/L, and > 100 µg/L. This study compared the serum levels of liver function markers including alanine transaminase (ALT), aspartate transaminase (AST), gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), total protein (TP), albumin (ALB), total bilirubin (TBIL), direct bilirubin (DBIL), and indirect bilirubin (IBIL) were compared among populations in areas with different water iodine concentrations. Significant differences were found in the levels of AST, ALP, TP, ALB, TBIL, DBIL, and IBIL. Based on different WIC, the chi-square test was employed to assess the prevalence of abnormal circulating liver function indicators. To further explore the association between different environmental WIC and these abnormal circulating liver function indicators, a logistic regression model was employed in this investigation. The results showed that following adjustment for potential confounders, both WIC< 10 µg/L and WIC> 100 µg/L were significantly negatively correlated with abnormal serum TP and ALB levels [WIC< 10 µg/L: odds ratio (OR), 3.147 (1.828,5.604), P < 0.001, OR, 4.149 (2.246,8.146), P < 0.001; WIC> 100 µg/L: OR, 2.456 (1.394,4.435), P = 0.002, OR, 2.211 (1.151, 4.425), P = 0.020]. Mediation analysis indicated direct associations between WIC and abnormal serum TP and ALB levels. Additionally, after excluding participants with thyroid dysfunction, identical analyses were conducted, and the observed associations showed no substantial changes in their nature.In conclusion, environmental WIC exposure was closely associated with abnormal liver function, showing a U-shaped association with abnormal serum TP and ALB levels. However, given the observational nature of this study, further mechanistic validation is warranted through in vivo and in vitro experiments to delineate the causal relationship.